Evaluation of salivary catalase, vitamin C, and alpha‐amylase in smokers and non‐smokers: a retrospective cohort study. (1st November 2016) - Ahmadi‐Motamayel, Fatemeh; Falsafi, Parisa; Goodarzi, Mohammad Taghi; Poorolajal, Jalal
Abstract : Background: Saliva and its defence systems such as antioxidants and minerals are very important in the pathogenesis of different diseases. Cigarette smoking has many destructive effects. Oxidative stresses play an important role in the side effects of smoking. This study assessed the effect of cigarette smoking on salivary levels of catalase, vitamin C, and α‐amylase. Methods: This retrospective cohort study was carried out in Hamadan, Iran, on 510 subjects; 259 subjects were smokers (the exposed group) and 251 were non‐smokers (the unexposed group). Five microliters of unstimulated saliva was collected by spitting method. Catalase, vitamin C, and α‐amylase salivary levels were determined by spectrophotometric assay. Data were analyzed with t ‐test using STATA 12. Results: Vitamin C level in smokers was significantly lower than that in non‐smokers. The salivary catalase levels were lower and α‐amylase levels were higher in smokers, but the differences were not statistically significant ( P = 0.416 and P = 0.265, respectively). Smokers were younger than non‐smokers. Conclusion: Smoking resulted in a change in salivary antioxidant levels. Changes in antioxidant levels can influence the deleterious effects of smoking on oral mucosa; it might also indicate systemic changes and changes in the serum levels of oxidative agents. Further studies are necessary to understand the mechanisms and real effects of smoking, to determine the benefits of supplementary antioxidants for treatment and to reduce the dangerous side effects of smoking.